Surveying the Greek chora : Black Sea region in a comparative perspective - Bilde, Pia Guldager; Stolba, Vladimir F. (Black Sea studies, 2006)
This volume is the outcome of an international conference on landscape archaeology. It includes 15 contributions from participants from six different countries, who analyse the territories of the main ancient cities of the west, north and south coasts of the Black Sea region, discussing them also in a comparative, Mediterranean perspective. The particular aim of the conference was to join the forces of Eastern as well as Western researchers in establishing an overview of the relationship between the larger ancient cities and their territories.